Combined experimental observation and numerical simulation of the cloud cavitation with U-type flow structures on hydrofoils. (March 2016) - Peng, X.X.; Ji, Bin; Cao, Yantao; Xu, Lianghao; Zhang, Guoping; Luo, Xianwu; Long, Xinping
Highlights: Spatial–temporal evolution of the cloud cavity is observed by HSV. U-type structure is the main flow structure during the cloud cavitation development. Some physical mechanism of cloud cavitation is clarified. Abstract: Sheet/cloud cavitation is an important topic that is a very common type of cavitation in turbo-machinery and marine propeller. Up to now we still have limited understanding of the cavitation shedding dynamics and cloud cavity formation and development. The present study used experimental and numerical studies to gain a better understanding of the complex physics involved in this problem. A series of experimental observations around hydrofoils are carried out in the cavitation tunnel of the China Ship Scientific Research Center (CSSRC) to illustrate the spatial–temporal evolution of the cloud cavity in detail. The results demonstrate that U-type flow structures are common in cloud cavities and can be divided into three stages and the closure line in a sheet cavity often has a convex–concave profile. Reentrant flows occur in the convex region with the jet direction normal to the contour edge so the shedding is mainly caused by the converging reentrant flows. Further analysis demonstrated that there was a striking difference with the cavity growth suppressed substantially in the twisted hydrofoil case if compared with straight hydrofoil and the effect of side entrant jets might make the cavity more uniform across the span. Numerical simulations were used to simulate the formation and development of the cloud cavity. The results show that the strong adverse pressure gradient in the stagnation region at the downstream end of the attached cavity forces the re-entrant flows into the vapor structure with a radially-diverging re-entrant jet and a pair of side-entrant jets, which causes the cavity shedding. Further analyzes of the local flow fields show that the interactions between the circulating flow and the shedding vapor cloud may be the main reason for the formation of the U-type cloud cavity structures. Graphical abstract: